Stark Broadening of Spectral Lines in Plasmas - Eugene Oks (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Experimental and theoretical studies of Stark broadening of spectral lines in plasmas are the cornerstone of a large number of spectroscopic diagnostics of laboratory and astrophysical plasmas. As such, they are very important both fundamentally and practically, the latter being due to the numerous practical applications of plasmas. Examples are studies dealing with: controlled thermonuclear fusion (that would provide a virtually unlimited source of energy), plasma-based lasers for medical and other purposes, technological microwave discharges (especially those used for manufacturing microchips), a better understanding of solar activity, other astrophysical objects (white dwarfs, flare stars, and so on). The book reviews advances in this area achieved in recent years and presents new original papers building on these advances.